The math book : from pythagoras to the 57th dimension, 250 milestones in the history of mathematics - Pickover, Clifford A. (New York : Sterling, 2009)
An anthology of descriptions of 250 significant achievements in the history of mathematics, arranged chronologically from circa 150 million BC to 2007.
Includes bibliographical references (p. 518-525) and index.
Adult
Keywords: Mathematics -- History; Mathematics -- History